How Much Progress Do Children in Shanghai Make Over One Academic Year? Evidence From PISA. (November 2016) - Anders, Jake; Jerrim, John; McCulloch, Andrew
Since its entry into the Programme for International Student Assessment (PISA) in 2009, the Chinese province of Shanghai has been the top-performing economy within these international rankings. Many have interpreted this as demonstrating how Shanghai has a "world class" education system, the most effective teaching methods, and the best schools. This article questions such interpretations of the PISA results. Specifically, we argue that statements about school and school system quality require information on the progress that children make during their time at school, which the PISA rankings do not provide (at least not directly). Our empirical analysis then uses a "fuzzy" regression discontinuity design approach to demonstrate how a rather different perspective of Shanghai's performance in PISA emerges once pupils' academic progress over one particular school year is considered. Our key finding is that the first year of upper secondary school in Shanghai adds essentially no value (on average) to children's PISA reading, science, and mathematics test scores.